2013
DOI: 10.1016/j.trf.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive workload and driving behavior in persons with hearing loss

Abstract: Results: HL had no effect on driving behavior at Baseline driving, where no events occurred.Both during Secondary task and at the Parked car event HL was associated with decreased mean driving speed compared to baseline driving. The effect of HL on the Secondary task performance, both at Baseline driving and at the lower Difficulty Level at Critical events, was more skipped letters and fewer correctly recalled letters. At Critical events, task difficulty affected participants with HL more. Participants were ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…With previous assumptions that driving is mostly a visual task [17], that deaf people have enhanced peripheral vision [14], and that drivers with HL show more cautious driving behavior [13], it is interesting that drivers with HL show worse driving performance during distraction than drivers with NH [1]. The purpose of the present study is to compare visual behavior in older adults with and without HL during normal driving and driving while performing a secondary task.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…With previous assumptions that driving is mostly a visual task [17], that deaf people have enhanced peripheral vision [14], and that drivers with HL show more cautious driving behavior [13], it is interesting that drivers with HL show worse driving performance during distraction than drivers with NH [1]. The purpose of the present study is to compare visual behavior in older adults with and without HL during normal driving and driving while performing a secondary task.…”
Section: Introductionmentioning
confidence: 95%
“…There was also a parked car event in which the drivers had to brake. Analysis of the data surrounding these events as well as driving performance is presented in a separate paper [13] and thus excluded here.…”
Section: Simulator Scenario and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, those who have issues with multitasking may well adapt their behaviour and withdraw from the auditory task in order to increase their road safety. Indeed, Thorslund et al (2013a;2013b;2014) have repeatedly observed, what they argue, is an adaptive driving style in their hearing impaired participants.…”
Section: Discussionmentioning
confidence: 97%